Makna Budaya Pada Bikago yang Mengandung Prefiks O- dan Go- Dalam Bahasa Jepang - Dhiya Fithriyana; Idah Hamidah; Hartati Hartati (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2020)
This study examines the cultural significance of bikago that contains the prefix o- and go- in Japanese (anthropological linguistic studies). The purpose of this study is to describe the cultural significance that lies behind the use of the prefix o- and go- on bikago in Japanese (Anthropological Linguistic Study).Theories used in this research are culture, anthropological linguistics, morphology, cultural meaning, whorf sapor hypothesis, nouns and o- and go- prefix theories. The type of method used is a qualitative description with a method of collecting data collected from various books, namely the book Minna no Nihonggo Shokyuu I & II, Minna no Nihonggo Yasashi Sakubun and Basic Kanji Vol II and observations validated by native speakers. The results of this study are vocabularies beginning with o- and go- thirty-two vocabularies all included in the futsuumeishi category 'noun that states a matter or object'. Futsuumeishi ‘noun stating a case or object’ consists of settogo ya setsubigo no tsuita mono (nouns added to the prefixes o- and go-). Data were analyzed based on the meaning of the dictionary and validated by native (Japanese) with informal interview techniques. The conclusion from the results of this study is that every noun or word containing the prefix o- and go- has a cultural meaning with a group and family concept.